Dishonest or professional behavior? Can we tell? A comment on: Cohn et al. 2014, Nature 516, 86-89, "Business culture and dishonesty in the banking industry" - Thomas Stöckl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
By means of a coin tossing experiment Cohn et al. (2014, Nature 516, 86-89, doi:10.1038tinature13977) study business culture in the banking industry and report that employees of a large, international bank behave honestly in a control condition while a significant proportion of them becomes dishonest when their professional identity as bank employees is rendered salient. The authors conclude that the business culture in the banking industry weakens and undermines the honesty norm. We argue that the data allows for an alternative interpretation based on so far unrecognized dynamics in the experimental design. This interpretation classifies bankers' behavior in the treatment condition to be in accordance with the professional requirements of the banking industry. The two competing interpretations cannot be flawlessly separated and, consequently, bankers' behavior cannot reliably be classified as resulting from a problematic business culture.
Keywords: G21; G28; C91; 330; experimental finance; dishonesty; business culture; banking industry